DNS Study of Initial-Stage Shock-Particle Curtain Interaction (Communications in Computational Physics, 2020)
High speed particulate flow appears in many scientific and engineeringproblems. Current work focuses on the situation with volume fraction of particlesbetween 0.001 and 0.5, in which both particle-fluid and particle-particle interactionsare important. Based on the stratified multi-phase flow model (Chang & Liou, J. Comput.Phys. 225 (2007), 840-873) with Euler equations, by regarding one phase as solid, anumerical method is developed to conduct direct numerical simulations (DNS) to highspeed particulate flows. It is then applied to simulate the problem with a planar shockwave impacting on a particle curtain, but focusing on the initial stage, in which theparticles can be regarded as static. 2-D simulations are conducted by keeping the totalvolume fraction of particles and changing the number of particles. The convergenceof shock wave locations and turbulent energy are observed. A 1-D volume-averagedmodel is also studied and compared with the DNS, which gives effective drag coefficients. A 3-D DNS is conducted to compare with the 2-D DNS and 1-D model, showingthat more detailed 3-D DNS studies are needed. The convergent values obtained fromcurrent work can be applied to the study of very small particle cases and to the modeldevelopment.